Molecular Docking and Molecular Dynamics Study of Phlorotannin-Derived Metabolites from Brown Macroalgae (Sargassum sp.) as Potential α-Amylase Inhibitors - Asnawi, Aiyi; Silviana, Lilis; Andriansyah, Ivan; Kurnia, Dewi; Febrina, Ellin; Dinata, Deden Indra (Jurnal Kimia Riset, 2025)
Type 2 diabetes mellitus (T2DM) is a widespread global health issue, characterized by insulin resistance and impaired a-amylase activity—an enzyme essential for carbohydrate metabolism. Phenolic compounds derived from brown macroalgae have been identified as potential a-amylase inhibitors and are promising candidates for the development of novel antidiabetic agents. This study aimed to explore the molecular interactions between phlorotannin-derived metabolites from Sargassum sp. and the α-amylase enzyme (PDB ID: 1B2Y) through in silico approaches, including molecular docking and molecular dynamics simulations. Molecular docking was performed using AutoDock 4.2, followed by molecular dynamics (MD) simulations using GROMACS to assess the stability of the ligand–enzyme complexes. The results revealed that dieckol (S06) and 6,6′-bieckol (S07) showed the strongest binding affinity with a docking score of -9.57 and -8.95 kcal/mol, respectively and the most favorable binding free energy (ΔTOTAL -56.87 kcal/mol), suggesting its strong potential for stable interaction with the enzyme. These results highlight the potential of dieckol and 6,6′-bieckol as effective α-amylase inhibitors.